2019
DOI: 10.1097/brs.0000000000002917
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Proprioception and Pain and Disability in People With Non-Specific Low Back Pain

Abstract: Study Design. Systematic review with meta-analysis. Objective. To examine the association between proprioception and pain and disability in people with non-specific low back pain (NSLBP) and the impact of potential moderators on the strength of the association. Summary of Background Data. NSLBP is a common musculoskeletal disorder and a leading cause of disability. Proprioception deficit has been associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…By subgrouping according to symptoms' severity, low and very low certainty evidence suggests no difference in error variability, significantly greater AE in NSLBP patients, and inconsistent results regarding error direction. The lack of a dose-response relationship between proprioceptive deficit and pain and disability [19] can probably explain this variation and the significant or not effects can be attribute to sample characteristics, or diversity in methodology implemented in included studies. Very low certainty evidence suggests greater AE (medium effect) between NSLBP patients and asymptomatic individuals in a blindfolded repositioning task, and no difference with vision available.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…By subgrouping according to symptoms' severity, low and very low certainty evidence suggests no difference in error variability, significantly greater AE in NSLBP patients, and inconsistent results regarding error direction. The lack of a dose-response relationship between proprioceptive deficit and pain and disability [19] can probably explain this variation and the significant or not effects can be attribute to sample characteristics, or diversity in methodology implemented in included studies. Very low certainty evidence suggests greater AE (medium effect) between NSLBP patients and asymptomatic individuals in a blindfolded repositioning task, and no difference with vision available.…”
Section: Plos Onementioning
confidence: 99%
“…It has been suggested that these proprioceptive deficits might be associated with the underlying characteristics and mechanisms of NSLBP development [17,18]. However, the precise association between NSLBP and proprioceptive deficits is unclear, as spinal proprioceptive impairments are not correlated with pain and disability [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, existing studies on SoP, SpP, and BO were largely conducted on healthy subjects (Longo et al, 2008a;Fuentes et al, 2013;Longo, 2017), and clinical research has mostly investigated neurological conditions (Haggard and Wolpert, 2005;Pia et al, 2013Pia et al, , 2016, eating disorders (Keizer et al, 2011;Scarpina et al, 2014;Spitoni et al, 2015;Gadsby, 2017), and neuropathic pain syndromes such as Complex Regional Pain Syndrome-CRPS (Galer and Jensen, 1999;Förderreuther et al, 2004;Lewis et al, 2007;Reinersmann et al, 2013). A large body of literature on the field of MDRDs has instead investigated primary somatosensations (Tsay et al, 2015), mainly tactile acuity (Catley et al, 2013(Catley et al, , 2014Harvie et al, 2018) and proprioceptive precision (Stanton et al, 2016;Tong et al, 2017;Lin et al, 2019), referring generically to disturbances at the level of perception or mental representations. However, both two-point discrimination and joint repositioning error (two of the most frequently investigated tasks) cannot be considered as having a higher-order somatoperceptual involvement Hillier et al, 2015;Spitoni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the shoulder have shown a reduction in proprioception amongst subjects with joint laxity [9], in athletes undertaking overhead sports [10], in conjunction with shoulder pain [11], rotator cuff injuries [12] and amongst athletes who are fatigued [7,[13][14][15][16]. Although the role of proprioception in musculoskeletal disorders has been extensively researched in the lumbar and cervical spine [17][18][19] comparatively, there is limited research within the shoulder complex.…”
Section: Introductionmentioning
confidence: 99%